The Opportunity of Sovereign Blue Sukuk Issuance in Maritime Sectors: Case Study of Indonesia - Ramdhani, Fakhry Barly; Masruhen, Mohmed Firdaus bin; Ibrahim, M. Y.; Pramitha, Devinna; Lubis, Rusdi Hamka (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2022)
The sea potential in Indonesia is very abundant, but the water governance is still poor and still raises concern for the community regarding the threat of damage. This is due to the limited financing of the maritime sector in Indonesia. This research tries to give alternative financing by using Sovereign Blue Sukuk, which further analyses the factors of benefit and opportunity if implemented. The method used is ANP with Benefit, Opportunity, Cost, and Risk (BOCR) network approach. The biggest weight in the benefit is improving people's welfare. As for the opportunity, the biggest weight is adding Sharia investment instruments. The greatest weight on load is the cost of coordination between institutions. From the risk, side is operational risk. In general, the cost rate is greater than the benefit, opportunity, and also risk. Furthermore, the alternative strategy that can be done to minimize the cost and risk are (1) institutional coordination; (2) the empowerment of fishermen; (3) Identification of marine projects.